Description of BTEX concentrations with wind roses in Tehran city: the study of monitoring, GIS-zoning maps and risk assessment. Issue 9 (4th December 2021) - Dadban Shahamat, Yousef; Khani, Mohammad Reza; Ghahrchi, Mina
Abstract: In the present study, the emission of BTEX compounds has been investigated in a one-year period (2016–2017) in Tehran city. According to, 26 sampling stations were selected in different parts of the city and had been sampled in four seasons of year to determine the concentration of BTEX as well as other meteorological parameters such as temperature, humidity and wind speed. Spatial distribution analysis of BTEX was introduced by using the Inverse Distance Weighting (IDW) method in Arc GIS 10.3. Also, to determine the carcinogenic and non-carcinogenic risk of target compounds, Monte Carlo simulation was used. The results showed that the annual mean of benzene, toluene, ethylbenzene, m-xylene and o-xylene were 30.08 ± 21.97, 54.17 ± 40.29, 25.81 ± 15.21, 27.83 ± 19.1 and 23.16 ± 12.28 μg/m 3, respectively. According to the result, the maximum and minimum concentrations of BTEX were in the center and north of the city, respectively. Temporally, the maximum value of BTEX was 232.61 ± 123.93 µg/m 3 in the autumn and the minimum value was 57.88 ± 24.93 µg/m 3 in the spring. The result obtains from the inhalation lifetime cancer risk (LTCR) indicative the carcinogenic potential of benzene. Noncarcinogenic risk index, namely the hazard quotient (HQ) for all BTEX compound except benzene concentration in the autumn (1.55), were lower than 1 degree so they were not harmful to human health. Graphical Abstract: UF0001